Implementasi QR Code Berbasis Web Pada Sistem Informasi Buku Tamu dan Pemesanan Undangan di Zehan Invitation. - Darmanta Sukrianto; Dwi Oktarina; Hendri Maradona (Computer Science and Information Technology, 2024)
Zehan Invitation is a business that provides digital invitation services, established in 2021. The rapid development of digital technology in various fields has led to changes in work methods and easier access to desired information. This technological advancement requires businesses to keep up with trends in order to remain competitive. Currently, Zehan Invitation's digital invitation orders are still processed through WhatsApp, which has several limitations. Using WhatsApp, customers do not receive real-time updates on their digital invitations and the services offered by Zehan Invitation. Customers also often experience slow responses from Zehan Invitation when seeking information about their orders. The objective of this research is to develop a platform that utilizes QR codes as a means of ordering digital invitations and recording guest arrivals through Zehan Invitation's web-based services. The system development method follows a waterfall approach, consisting of data collection, data analysis, system analysis, system design, testing, and implementation. The research results indicate that this system successfully provides practical solutions for guest management and invitation ordering, while also enhancing process efficiency.